THE EFFECT OF CARBON EMISSION DISCLOSURE, GREEN INVESTMENT AND FINANCIAL PERFORMANCE ON COMPANY VALUE FOR MINING COMPANIES LISTED ON THE IDX FOR THE PERIOD 2019 – 2023 - Tyas, Hening (DAS CONFERENCE INTERNATIONAL SERIES, 2025)
This research aims to determine the effect of carbon emissions disclosure, green investment, and financial performance on company value in mining companies listed on the Indonesia Stock Exchange (BEI) in the 2019- 2024 period. This research uses a quantitative approach, with a population of 81 companies in mining companies that are still listed on the Indonesia Stock Exchange from 2019 to 2024, and the sample in this research is 16 companies where the sampling technique uses purposive sampling. The analysis technique used is panel data regression analysis with the help of the Eviews 12 program. The results of this research show that partially disclosure of carbon emissions has a positive effect on company value, the green investment variable has no effect on company value, and the financial performance variable has a positive effect on value. company.